Perceptions of youth-friendly sexual and reproductive health services in selected Higher and Tertiary Education Institutions of Zambia: A qualitative study on the perspectives of young people and healthcare providers. - Choolwe Jacobs; Flata Mwale; Musonda Mubanga; Mwenya Kasonde; Alice Saili; Remmy Mukonka; Lenard Mumbi Mwilu; Margarate Nzala Munakampe (Public Library of Science (PLoS), 2023)
The recognition of the need for Adolescent and Youth-Friendly Health Services (AYFHS) is growing. It is important to ensure the provision of high-quality sexual and reproductive health (SRH) services that cater to the unique needs of adolescents and young people (AYP). Adolescents and young people spend a significant amount of time in Higher and Tertiary Education Institutions (HTEIs) where adolescent friendly services are needed. However, there is limited evidence on the availability of sexual and reproductive health services for young people in HTEIs in Zambia. Using the Human Rights Based Approach to healthcare availability, accessibility, acceptability, and quality of care (AAAQ) framework, this study explores young people's perceptions of youth-friendly sexual and reproductive health services in selected HTEIs in Zambia. Between March and June 2021, a qualitative case study was conducted in 12 selected HTEIs located in Lusaka, Central, and Copperbelt provinces of Zambia. The study employed In-depth Interviews (IDIs) and Focus Group Discussions (FGDs) with AYPs, as well as Key-informant Interviews (KIIs) with healthcare providers. The healthcare providers at health facility, district and provincial levels were interviewed to provide insights about the services provided in the HTEIs. A total of 112 interviews were conducted. Data analysis was performed using thematic analysis in NVivo version 11. In the study, young people reported the availability of primary health services like malaria, HIV, and pregnancy testing, as well as screening for STIs. However, their awareness of SRH services was limited. Contraception, STI testing and treatment, and HIV and pregnancy screening and testing were the most accessed services. Equipment and commodity shortages were common, hindering care provision. Young people found healthcare services in educational institutions inaccessible, with limited comprehensive care and understanding from providers. Services lacked tailoring for key populations and privacy/confidentiality. Health care providers also reported inadequate youth-friendly spaces, equipment, medication and trained workers which compromised the quality of care. Peer educators and provider training were seen as essential for improving accessibility and acceptability of services. The findings indicate significant barriers to the accessibility, availability, and acceptability of SRH services for AYP in HTEIs in Zambia. There is a pressing need to enhance AYSRH programming by increasing awareness of services and ensuring their availability and accessibility for young people. Sufficient funding for AYFHS can address challenges related to service quality, including inconsistent availability of medical equipment and supplies. Building the capacity of service providers can potentially enhance the uptake of services by AYP. It is crucial to target services to address the specific vulnerabilities of students with disabilities and key populations, aligning with the goal of achieving universal health coverage and leaving no one behind.